The complete Milk Street TV show cookbook : 2017-2019 : every recipe from every episode of the popular TV show - Kimball, Christopher; Hirsch, J. M.; Card, Matthew; Locke, Michelle; Cox, Jennifer Baldino, 1972- (Little, Brown and Company, 2018)
For decades, Christopher Kimball has promised home cooks recipes that work. Now, with his team of cooks and editors at Milk Street, he promises that a new approach in the kitchen can elevate the quality of your cooking far beyond what you thought possible. Milk Street's techniques are simple and smart, resulting in flavors that are fresh yet familiar. You'll find instant classics like Thai Fried Rice, Cacio e Pepe, and Charred Brussels Sprouts alongside Harissa Roasted Potatoes and Cape Malay Chicken Curry, and you'll even discover a new way to make old favorites like Central Mexican Guacamole and Israeli Hummus. Organized by type of dish--from salads, soups, grains, and vegetable sides to simple dinners and 21st-century desserts--these recipes all deliver big flavors without your needing to learn a new culinary language. But these are more than just good recipes. They teach a simpler, bolder, healthier way to eat that will change your cooking forever, making it a pleasure rather than a chore.